Unveiling membrane thermoregulation strategies in marine picocyanobacteria. Issue 6 (11th November 2019) - Breton, Solène; Jouhet, Juliette; Guyet, Ulysse; Gros, Valérie; Pittera, Justine; Demory, David; Partensky, Frédéric; Doré, Hugo; Ratin, Morgane; Maréchal, Eric; Nguyen, Ngoc An; Garczarek, Laurence; et al.
Summary: The wide latitudinal distribution of marine Synechococcus cyanobacteria partly relies on the differentiation of lineages adapted to distinct thermal environments. Membranes are highly thermosensitive cell components, and the ability to modulate their fluidity can be critical for the fitness of an ecotype in a particular thermal niche. We compared the thermophysiology of Synechococcus strains representative of major temperature ecotypes in the field. We measured growth, photosynthetic capacities and membrane lipidome variations. We carried out a metagenomic analysis of stations of the Tara Oceans expedition to describe the latitudinal distribution of the lipid desaturase genes in the oceans. All strains maintained efficient photosynthetic capacities over their different temperature growth ranges. Subpolar and cold temperate strains showed enhanced capacities for lipid monodesaturation at low temperature thanks to an additional, poorly regiospecific Δ9‐desaturase. By contrast, tropical and warm temperate strains displayed moderate monodesaturation capacities but high proportions of double unsaturations in response to cold, thanks to regiospecific Δ12‐desaturases. The desaturase genes displayed specific distributions directly related to latitudinal variations in ocean surface temperature. This study highlights the critical importance of membrane fluidity modulation by desaturases in the adaptive strategies of Synechococcus cyanobacteria during the colonization of novel thermal niches.